2018
DOI: 10.1001/jama.2018.2408
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Post–Acute Care Use Among Medicare Beneficiaries: 2000 to 2015

Abstract: Since Medicare’s adoption of the inpatient prospective payment system in 1983, hospitals have sought ways to reduce costs, resulting in a decrease in hospital length of stay and an increase in the use of institutional post–acute care,1 making it a major Medicare expenditure.2 Since the Affordable Care Act passed in 2010, Medicare has implemented payment reforms designed to make hospitals and clinicians accountable for the cost and quality of care delivered. Examples include the Hospital Readmissions Reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
80
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 111 publications
(80 citation statements)
references
References 3 publications
0
80
0
Order By: Relevance
“…Some studies additionally observed a decline in SNF length of stay under alterative payment systems . Indeed, recent research has found that starting in 2015, SNF length of stay started to decline . Further reductions in postacute care use—both in SNF as a discharge destination and in length of stay once admitted to a SNF—are likely as health systems seek to further tamp down the costs of care and improve the value of the health care they deliver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies additionally observed a decline in SNF length of stay under alterative payment systems . Indeed, recent research has found that starting in 2015, SNF length of stay started to decline . Further reductions in postacute care use—both in SNF as a discharge destination and in length of stay once admitted to a SNF—are likely as health systems seek to further tamp down the costs of care and improve the value of the health care they deliver.…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, Medicare spent over $60 billion on postacute care, an amount that has rapidly increased in recent years. Over 40 percent of Medicare beneficiaries receive postacute care after a hospital discharge, the majority of which is in a SNF …”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, reported patient outcomes in the realms of functional abilities, morbidity, and mortality have been consistently better in IRFs than those from SNFs, even when controlling for multiple variables [20,21]. Despite these outcomes, acute hospital discharges to SNFs from 2000 to 2015 accounted for 85% of institutional post‐acute care with a total healthcare cost 3 times of that of IRFs [22]. This pattern is not likely to reverse in the foreseeable future given the national focus on reducing health care costs and moves to implement site‐neutral payments.…”
Section: Rehabilitation In the Subacute/snf Settingmentioning
confidence: 98%
“…As healthcare systems evolve to reduce hospital length of stay and expenditures, acute care patients are increasingly discharged to post‐acute care facilities, predominantly for short‐term rehabilitation and subsequent discharge home . Approximately 24% of such post‐acute care patients are readmitted to acute care facilities within 30 days .…”
mentioning
confidence: 99%